Patient-Derived Explants as a Precision Medicine Patient-Proximal Testing Platform Informing Cancer Management - Templeton, Abby R.; Jeffery, Penny L.; Thomas, Patrick B.; Perera, Mahasha P. J.; Ng, Gary; Calabrese, Alivia R.; Nicholls, Clarissa; Mackenzie, Nathan J.; Wood, Jack; Bray, Laura J.; Vela, Ian; Thompson, Erik W.; et al. (Frontiers in Oncology, 2021)
Precision medicine approaches that inform clinical management of individuals with cancer are progressively advancing. Patient-derived explants (PDEs) provide a patient-proximal ex vivo platform that can be used to assess sensitivity to standard of care (SOC) therapies and novel agents. PDEs have several advantages as a patient-proximal model compared to current preclinical models, as they maintain the phenotype and microenvironment of the individual tumor. However, the longevity of PDEs is not compatible with the timeframe required to incorporate candidate therapeutic options identified by whole exome sequencing (WES) of the patient’s tumor. This review investigates how PDE longevity varies across tumor streams and how this is influenced by tissue preparation. Improving longevity of PDEs will enable individualized therapeutics testing, and thus contribute to improving outcomes for people with cancer.